2021
DOI: 10.3389/fcell.2021.668164
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Fibroblasts Facilitate Squamous Cell Carcinoma Lung Metastasis in Mice by Providing TGFβ-Mediated Cancer Stem Cell Niche

Abstract: Cancer-associated fibroblasts (CAFs) have been shown to enhance squamous cell carcinoma (SCC) growth, but it is unclear whether they promote SCC lung metastasis. We generated CAFs from K15.KrasG12D.Smad4–/– mouse SCCs. RNA expression analyses demonstrated that CAFs had enriched transforming growth factor-beta (TGFβ) signaling compared to normal tissue-associated fibroblasts (NAFs), therefore we assessed how TGFβ-enriched CAFs impact SCC metastasis. We co-injected SCC cells with CAFs to the skin, tail vein, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…TGF-β signaling is one of the most important pathways influencing tumor initiation [ 37 ], growth [ 38 ], and metastasis [ 39 ]. Consistently, we observed that TGF-β activation is essential for lung metastasis growth in head and neck squamous cell carcinoma [ 40 ]. Currently, there are many agents designed to target TGF-β signaling that have achieved satisfying clinical cancer treatment efficacy [ 10 ].…”
Section: Characteristics Of the Tumor Metabolic Microenvironmentsupporting
confidence: 65%
See 1 more Smart Citation
“…TGF-β signaling is one of the most important pathways influencing tumor initiation [ 37 ], growth [ 38 ], and metastasis [ 39 ]. Consistently, we observed that TGF-β activation is essential for lung metastasis growth in head and neck squamous cell carcinoma [ 40 ]. Currently, there are many agents designed to target TGF-β signaling that have achieved satisfying clinical cancer treatment efficacy [ 10 ].…”
Section: Characteristics Of the Tumor Metabolic Microenvironmentsupporting
confidence: 65%
“…CAFs are the most abundant stromal cells that promote cancer growth and metastasis [ 10 , 148 , 149 ]. Glucose metabolism reprogramming in CAFs is mainly involved in glycolysis and the TCA cycle.…”
Section: Tgf-β-dependent Metabolism Of Stromal–epithelial Coupling An...mentioning
confidence: 99%
“…Similar to the in-vivo TME condition, the external microenvironment of in-vitro cell cultures also influences their gene expression pattern, metabolic requirements, and signalling pathways ( 33 ). For instance, co-culture of cancer cells with CAFs leads to the promotion of stem-cell-like properties in squamous cell carcinoma ( 34 ), cancer cells and their exosomes derived TGF-β augmented proliferation and expression of CAF markers ( 35 ), and the co-culture of pancreatic cancer cells with monocytes and fibroblasts induces the production of immunosuppressive cytokines which are known to promote polarization towards M2 like macrophages and myeloid-derived suppressive cells (MDSCs) ( 36 ). All these reports highlighted the importance of developing in-vitro tumorigenic 3D cultures to imitate the in-vivo TME features and establish tumor-stroma interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Epidermal growth factor (EGFR) is involved in the control of multiple pathways that mediate both proliferation and invasion and migration. EGFR also modulates tumor survival and angiogenesis, and EGF-induced STAT3 signaling initiates the transcription of genes that modulate cell growth, survival, and angiogenesis (Cyclyn D1, Bcl-XL, and VEGF, respectively) [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Progression and metastasis involve the interaction of the tumor with the tumor microenvironment and the remodeling of it and the stromal cells, a cytokine-mediated interaction.…”
Section: Microrna Involvement In Head and Neck Cancer Developmentmentioning
confidence: 99%